Takfiri Dalam Kitab Hamyan Al-Zad Ila Dar Al-Ma’ad Karya Muhammad Bin Yusuf Itfisy - Hidayat, Hamdan (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2020)
This paper will discuss about takfir in the commentary book Hamyan al-Zad Ila Dar al-Ma'ād by Muhammad bin Yusuf Itfisy. The study of the book Hamyan Al-Zad Ila Dar Al-Ma'ād is considered important, because this book contains interpretation of verses that contain takfir according to the views of the Khāwarij sect of the al-Ibadiyah sect. As we know, the Khāwarijs were a very easy people to justify disbelievers against others who were not in line with the Khāwarijs. In the realm of al-Qur'an exegesis, the Koran will be interpreted according to its interpreter, as well as in the commentary book of Hamyan Al-Zad Ila Dar Al-Ma'ād the verses of the Koran are interpreted for the benefit of the Khāwarij group as legitimacy. So this kind of interpretation is called tafsir al-I'tiqadi.